2006
DOI: 10.1007/s11434-005-1087-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling under different photoperiod/temperature conditions in a photoperiod-/thermo-sensitive genic male sterile line of rice (Oryza sativa L.)

Abstract: Peiai 64S is a photoperiod-and thermosensitive genic male sterile (PTSGMS) line of rice, which is male sterile at long day/high temperature and partial fertile at short day/low temperature. A cDNA array representing 3328 unique rice genes was used to profile the gene expression patterns in the young panicles of Peiai 64S under these two conditions. The statistical data showed that up to 14.60% of genes exhibited up-or down-regulated expressions in the plants at long day/high temperature compared with plants at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Thus, LOC_Os07g 12130 that may be regarded as a member of a signal transduction pathway affects anther development by regulating gene expression at different temperatures. In young panicles of Pei′ai64S, Myb transcription factors showed a significantly lower transcriptional abundance under the LD/HT than under the SD/LT conditions, which may lead to a significant gene inhibition in the normal process of transcription (Guo et al, 2006).…”
Section: Correlation Between Myb-like Protein and Ptgms Genementioning
confidence: 94%
“…Thus, LOC_Os07g 12130 that may be regarded as a member of a signal transduction pathway affects anther development by regulating gene expression at different temperatures. In young panicles of Pei′ai64S, Myb transcription factors showed a significantly lower transcriptional abundance under the LD/HT than under the SD/LT conditions, which may lead to a significant gene inhibition in the normal process of transcription (Guo et al, 2006).…”
Section: Correlation Between Myb-like Protein and Ptgms Genementioning
confidence: 94%
“…Description of preparation, analysis and quality control of cDNA array can be found in the published papers of our laboratory (Deng et al, 2006;Dong et al, 2005;Guo et al, 2005).…”
Section: Quality Controlmentioning
confidence: 99%
“…Two PISTILLATA (PI)-type class-B MADS-box genes, WPI1 and WPI2, and class D MADSbox genes, as well as WPPK1 (wheat pistillody-related protein kinase 1) were shown to be associated with the formation of pistil-like stamens in alloplastic wheat (Hama et al 2004;Saraike et al 2007). The distinct up-and downregulated expression changes of genes encoding MMK1 and MMK2 were observed at different day length/temperature regimes by Guo et al (2006), and suggested that the signal transduction pathway mediated by MAPK might be involved in the process regulating gene expression during fertility reversion. The wtms1 gene responsible for the sterility of the thermo-sensitive genic male-sterile wheat line BNY-S was mapped to chromosome 2B, and the transcript level of the candidate gene, TaAPT2, was decreased significantly in the young spikelets at an early stage of pollen development under low temperature stress (Xing et al 2003(Xing et al , 2005.…”
Section: Introductionmentioning
confidence: 98%